Effect of seasonal infertility period on boar sperm proteins and quality characteristics - MICHOS, I.A.; TSAKMAKIDIS, I.A.; TSANTARLIOTOU, M.; TSOUSIS, G.; HADWEH, P.; BOSCOS, C.M. (Journal of the Hellenic Veterinary Medical Society, 2020)
Swine seasonal infertility reduces the productivity and profitability of a pig farm. The main causes of this condition are elevated environmental temperatures and long photoperiod during the summer season. The aim of this study was to investigate which sperm proteins and parameters are affected during the period of seasonal infertility. Depending on the environmental temperatures, the period from October to June was considered as cold and the period from July to September as warm season. A total of 65 ejaculates from 18 boars were collected over a year. Each semen sample was evaluated for kinetics (Computer Assisted Semen Analyzer), morphology (Sperm Blue stain), viability (Propidium Iodide - Calcein AM stain), mitochondrial membrane potential (Rhodamine 123 – Propidium Iodide stain), membrane integrity and functionality (Hypo-osmotic swelling test) and sperm DNA integrity (Acridine Orange Test). Moreover, selected proteins (HSP90, GPX5, OPN) were detected and quantified. The kinetic parameters VSL, LIN and the midpiece abnormalities were significantly higher in the warm compared to the cold season (p<0.05), while a strong tendency towards higher values for HSP90 and GPX5 was observed in warm compared to cold season (p=0.07and p=0.06, respectively). In conclusion, among the boar sperm characteristics tested in our study, seasonal infertility period negatively affected VSL and LIN kinetics, while GPX5 seminal plasma enzyme and HSP90 sperm surface protein increased their sperm protective effects.